2016
DOI: 10.3892/mmr.2016.5202
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-199a-5p inhibits tumor proliferation in melanoma by mediating HIF-1α

Abstract: The expression of hypoxia-inducible factor 1α (HIF-1α) is often abundant in human cancer and it is associated with poor prognosis. The present study aimed to investigate its regulation by microRNA (miRNA). The expression of miRNA-199a-5p (miR-199a-5p) in melanoma was detected by quantitative polymerase chain reaction on samples from 25 melanoma patients. The target of miR-199a-5p was predicted and demonstrated by a dual‑luciferase reporter system. The effects of miR-199a-5p on melanoma cells were assayed in B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…To date, miR-199a has been mostly studied for its roles in cardiac hypertrophy,46, 47 smooth muscle proliferation, 48 angiogenesis,49, 50, 51, 52, 53, 54 and as a tumor suppressor in a variety of cancers 29, 50, 52, 55, 56, 57, 58, 59. However, miR-199a also regulates several genes important for arteriogenesis via direct seed sequence binding to target mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, miR-199a has been mostly studied for its roles in cardiac hypertrophy,46, 47 smooth muscle proliferation, 48 angiogenesis,49, 50, 51, 52, 53, 54 and as a tumor suppressor in a variety of cancers 29, 50, 52, 55, 56, 57, 58, 59. However, miR-199a also regulates several genes important for arteriogenesis via direct seed sequence binding to target mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested an association between miR-320 and HIF-1α in adjusting RB progression. Increasing evidence has shown that miRNA interfere with the metastasis and invasion of various types of cancer via the regulation of HIF-1α (21)(22)(23)(24). In this study, a luciferase reporter assay was employed to investigate the effect of miR-320 on HIF-1α.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that miRNAs function via regulating their target protein by binding to the 3’ untranslated regions (UTRs) of target messenger RNAs (mRNAs), resulting in mRNA degradation or the blockade of mRNA translation . Previously, miR‐199a‐5p was reported to functions as a tumor suppressor by targeting connective tissue growth factor (CTGF), integrin β1, hypoxia‐inducible factor 1 alpha (HIF‐1α), E‐cadherin, hexokinase 2, frizzled class receptor 6 (FZD6), E2F transcription factor 3 (E2F3), Wnt family member 2 (WNT2) and cyclin‐dependent kinase inhibitor 1C (P57, CDKN1C) …”
Section: Discussionmentioning
confidence: 99%
“…In present study, we showed that miR-199a-5p, frequently down- 19,20 Previously, miR-199a-5p was reported to functions as a tumor suppressor by targeting connective tissue growth factor (CTGF), integrin β1, hypoxia-inducible factor 1 alpha (HIF-1α), E-cadherin, hexokinase 2, frizzled class receptor 6 (FZD6), E2F transcription factor 3 (E2F3), Wnt family member 2 (WNT2) and cyclin-dependent kinase inhibitor 1C (P57, CDKN1C). [21][22][23][24][25][26][27][28][29] Clathrin is considered the prototype vesicle coat protein whose self-assembly mediates sorting of membrane cargo and recruitment of lipid modifiers. 30 In the past decades, most of studies were focused on clathrin mediated endocytosis.…”
Section: Discussionmentioning
confidence: 99%